Sluggishness of Early-Stage Face Processing (N170) Is Correlated with Negative and General Psychiatric Symptoms in Schizophrenia - Zheng, Yingjun; Li, Haijing; Ning, Yuping; Ren, Jianjuan; Wu, Zhangying; Huang, Rongcheng; Luan, Guoming; Li, Tianfu; Bi, Taiyong; Wang, Qian; She, Shenglin (Frontiers in Human Neuroscience, 2016)
Patients with schizophrenia exhibit consistent abnormalities in face-evoked N170. However, the relation between face-specific N170 abnormalities in schizophrenic patients and schizophrenia clinical characters, which probably based on common neural mechanisms, is still rarely discovered. Using event-related potentials (ERPs) recording in both schizophrenic patients and healthy controls, the amplitude and latency of N170 were recorded when participants were passively watching face and non-face (table) pictures. The results showed a face-specific N170 latency sluggishness in schizophrenic patients, i.e., the N170 latencies of schizophrenic patients were significantly longer than those of healthy controls under both upright face and inverted face conditions. Importantly, the face-related N170 latencies of the left temporo-occipital electrodes (P7 and PO7) were positively correlated with negative symptoms and general psychiatric symptoms. Besides the analysis of latencies, the N170 amplitudes became weaker in schizophrenic patients under both inverted face and inverted table conditions, with a left hemisphere dominant. More interestingly, the FIEs (the difference of N170 amplitudes between upright and inverted faces) were absent in schizophrenic patients, which suggested the abnormality of holistic face processing. These results above revealed a marked symptom-relevant neural sluggishness of face-specific processing in schizophrenic patients, supporting the demyelinating hypothesis of schizophrenia.